Effects of composite casein and β-lactoglobulin genotypes on renneting properties and composition of bovine milk by assuming an animal model - Ikonen, Tiina; Ojala, Matti; Syväoja, Eeva-Liisa (Agricultural and Food Science, 1997)
The effects of κ-β-casein genotypes and β-lactoglobulin genotypes on the renneting properties and composition of milk were estimated for 174 and 155 milk samples of 59 Finnish Ayrshire and 55 Finnish Friesian cows, respectively. As well as the random additive genetic and permanent environmental effects of a cow, the model included the fixed effects for parity, lactation stage, season, κ-β-casein genotypes and κ-lactoglobulin genotypes. Favourable renneting properties were associated with κ-β-casein genotypes ABA1A2, ABA1A1 and AAA1A2 in the Finnish Ayrshire, and with ABA2B, AAA1A3, AAA2A3, ABA1A2 and ABA2A2 in the Finnish Friesian. The favourable effect of these genotypes on curd firming time and on firmness of the curd was partly due to their association with a high κ-casein concentration in the milk. The effect of the κ-casein E allele on renneting properties was unfavourable compared with that of the κ-casein B allele, and possibly with that of the A allele. The β-lactoglobulin genotypes had no effect on renneting properties but they had a clear effect on the protein composition of milk. The β-lactoglobulin AA genotype was associated with a high whey protein % and β-lactoglobulin concentration and the BB genotype with a high casein % and casein number.